Self-performed glansectomy and surgical repair by a nonpsychotic patient on androgen replacement therapy - Roth, Kirk; Izard, Jason; Beiko, Darren (Canadian Urological Association Journal, 2013)
Genital self-amputation in men is a rare condition. We report an interesting case of penile self-amputation that was performed and surgically repaired by a nonpsychotic patient who was enrolled in a clinical trial for androgen replacement therapy. Using sterile technique for amputation of the glans penis and using cotton thread to suture the wound, the patient was able to avoid hemorrhage and infection. This is the first reported case of androgen therapy– induced penile self-amputation with patient-performed surgical reconstruction using primitive instruments.